Vib-phages as a supportive tool for development of antibacterial treatment in aquaculture - Hamdan, Ruhil Hayati; Tan, Li Peng; Mat Zin, Ain Auzureen; Mohamad, Nora Faten Afifah; Pang, Sing Tung; Hamid, Nur Hidayahanum; Lee, Rui Ying (Universiti Teknologi MARA, Kedah, 2023)
Vibrio infections play a leading role in constraining the sustainable growth of the aquaculture sector worldwide and, consequently, are the target of manifold disease prevention strategies. During the early, larval stages of development, Vibrio species are a common cause of high mortality rates in reared fish. Antibiotic resistance is increasing among Vibrio species, with the use of phages constituting a promising, sustainable approach to prevent Vibrio infections in aquaculture. Vib-Phages is an alternative antibacterial treatment for Vibriosis. It can be used directly in fish feed or water.